(untitled) (Third Sector Social Economic Review, 2023)
The aim of this research is to examine the change in the perceptions of primary school 1st grade students by concept teaching techniques for the concepts of the ""Life in Our Country"" unit in the primary school 1st grade Life Sciences course. Action research which is one of the qualitative research methods was used in this study. The study group of the research consisted of 20 students that studied in the first grade of an official primary school in Zara district of Sivas province in the 2021-2022 academic year. These students were selected by criterion sampling and easily accessible sampling methods. Pre-perception form, post-perception form and student interview forms were used to collect data. Content analysis method was used for the analysis of the obtained data. Research findings have indicated that all of the students have given answers towards the concepts; “the neighborhood, the village, the War of Independence, the nation, capital, national day, national holiday, ceremony, celebration, national assembly, democracy, religion, a religious holiday”, vast majority of the students have given answers towards the concepts; “the tourists, nature, culture, district, county, date, republic, flag of independence”, a majority of the students have given answers towards the concepts of “state and country” based on concept teaching. As a result of the research, it was determined that concept teaching based on concept teaching techniques created teaching-based changes in students’ perceptions of concepts.